Diagnostic accuracy of diffusion-weighted imaging in differentiating glioma recurrence from posttreatment-related changes: a meta-analysis. Issue 1 (2nd January 2022) - Du, Xiaoli; He, Qian; Zhang, Boli; Li, Na; Zeng, Xuewen; Li, Wenbo
ABSTRACT: Background: Magnetic resonance imaging (MRI) is the most commonly used imaging method to evaluate glioma recurrence. However, conventional MRI has difficulty distinguishing glioma accurately. This study aimed to explore the value of diffusion weighted imaging (DWI) in evaluating glioma recurrence and post-treatment-related changes. Research design and methods: PubMed, Cochrane Library, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang Database and China Science and Technology Journal Database were extensively searched in accordance with inclusion criteria and exclusion criteria to obtain appropriate included studies. The quality of the included studies was evaluated using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool. Combined sensitivity and specificity and the area under the summary receiver operating characteristic curve (SROC) with the 95% confidence interval (CI) were calculated. Results: Seventeen high-quality studies were included. The combined sensitivity was 0.82 (95% CI: 0.76–0.87), the specificity was 0.83 (95% CI: 0.76–0.89), the positive likelihood ratio was 4.9 (95% CI: 3.2–7.5), the negative likelihood ratio was 0.21 (95% CI: 0.15–0.30), the diagnostic odds ratio was 23 (95%: CI 11–48), and the area under the SROC was 0.90 (95% CI: 0.87–0.92). Conclusions: This meta-analysis suggests that DWI has high sensitivity, specificity and accuracy in differentiating glioma recurrence.